Caracterização socioambiental e uso de animais por comunidades tradicionais do litoral do Estado do Ceará - Pinto, Márcia Freire (2012)
There is considerable interest in the integrity and environmental equilibrium of coastal regions as they are home to approximately 2/3 of the world s population - including many traditional communities that are directly dependent on local natural resources for their survival and economic welfare. It is within this context that the present ethnobiological study analyzed the use of native animals in the region around Icapuí to better understand the relationships between human communities and their surrounding environments and to aid in developing public policies and actions directed towards sustainability. Icapuí is located on the eastern coast of Ceará State, Brazil, and comprises 16 coastal fishing communities that are characterized principally by traditional fishing activities and by the relationships they have established with the sea, as well as 22 rural communities that depend agriculture and animal husbandry. The villages of Córrego do Sal and Redonda were chosen to undertake the present ethnozoological research. The methodologies employed included bibliographic research, observations, interviews, reunions with focal groups, the free-listing technique, the use of photographs and drawings to confirm the identification of the animal species, community mapping, and non-specific induction and new reading. The following activities were undertaken: general characterizations of how the communities at Icapuí use local natural resources and occupy that space; a socio-environmental diagnosis of the Córrego do Sal community; participatory mapping of the Córrego do Sal community; and ethnozoological inventories of the Córrego Sal and Redonda communities. The fisherman interviewed in Redonda cited 176 marine animals, corresponding to 329 species (of which 11 could only be identified to the genus level). A total of 156 fish were cited (87% of all of the animals mentioned), corresponding to 292 species. A total of 96 animals were cited by the residents of the Córrego do Sal agricultural community, corresponding to 108 species (of which two could only be identified to the genus level). There were visible differences between the communities at Icapuí that were related to their individual modes of community life, even in spite of many external influences and the incorporation of new cultural values. The use of biological resources by the different communities at Icapuí varied principally according to their immediate environments (whether coastal or interior sites). The traditional knowledge retained by these social groups will be of significant importance in establishing local policies that can help guarantee the sustainability of the activities undertaken by these communities, their well-being, and the conservation of native animal species.